Descriptive analysis of pecan cultivars, a comparison of raw and roasted pecans, and how pecan flavor changes over time - Magnuson, Shelby M. (Kansas State University, 2015)
Pecan [Carya illinoinensis(Wangenh.) K. Koch] is a native North American nut tree that has progressed into a significant agricultural crop. Flavor characteristics were evaluated for sixteen pecan cultivars: ‘Giles’, ‘Hirschi’, ‘Maramec’, ‘Oswego’, ‘Lakota’, ‘Chetopa’, ‘Colby’, ‘Witte’, ‘Dooley’, ‘Kanza’, ‘Pawnee’, ‘Stuart’, ‘Chickasaw’, ‘Peruque’, ‘Major’, and ‘Henning’ using descriptive sensory analysis. A trained panel consisting of six panelists first developed a vocabulary for the raw pecans and scored the intensities of the samples for 20 flavor attributes. Results showed that the sixteen samples differed significantly (P ≤ 0.05) on 10 of the attributes. ‘Giles’, ‘Lakota’, and ‘Pawnee’ differed from the other 13 cultivars for the majority of the attributes. The remaining thirteen cultivars showed few differences in individual attribute ratings, but did show differences when mapped using multivariate techniques indicating as many as two clusters of pecan cultivars based on flavor. The same sixteen cultivars were then roasted and evaluated using descriptive sensory analysis by the same trained panel using the same 20 flavor attributes. Three texture attributes were also evaluated. These results were compared to the results from the raw pecans. Results showed that 4 attributes differed significantly across all cultivars when raw and roasted flavor was compared. Ten of the flavor attributes had higher intensities for the roasted pecans than for the raw pecans. Most of these attributes fell within the categories of ‘nutty’ and ‘sweet’. When pecans were roasted many flavor attributes were intensified, as compared to when they were raw. How the flavor of the sixteen cultivars changed over a 12 month period was then evaluated. Raw pecans were evaluated when fresh, at 3 months, 6 months, 9 months, and 12 months by descriptive sensory analysis. A trained six member panel evaluated four flavor attributes at all five time points. Results showed that bitter had the highest intensity scores for all 16 cultivars at all 5 time points. Rancidity increased over time and sweetness decreased over time for all attributes. The results from these studies can be used as a baseline for future pecan research.
Keywords: Sensory; Descriptive analysis; Pecan; Food Science (0359)